Plasma - Paul, Bradley (Pitt poetry series., 2018)
The poems in Plasma, Bradley Paul's third book, use common objects, animals, people, and experiences as starting points to consider one's connectivity to the world. Riddles and obituaries alternate with rants and memories of things that never existed or that the speaker has never seen -- or that he has, and struggles to remember. The title is inspired by all our conceptions of plasma: an infinitely conductive state of matter in which the many disparate parts act collectively to create a single, ever-shifting whole. The part of the blood that communicates and provides. The ethereal medium by which we watch thousands of electronic images, sounds, and stories.